Laicity in brazilian I Republic: the orthodox positivists - Lacerda, Gustavo Biscaia de (Universidade Estadual Paulista / UNESP, 2017)
The present article aims to expose some of the leading ideas defended, in different times, by the brazilian orthodox positivists, i. e., by the members of the Brazilian Positivist Church and Apostolate. The ideas analyzed have been exposed in texts publicated in 1887, 1906 and 1913, authored by Raimundo Teixeira Mendes, and has as main theme what orthodox positivists called “separation of the two powers” (Temporal and Spiritual) – which could be named nowadays “State laicity” (although quite imperfectly). After some considerations on the publications’s style, the article expose the arguments of publications n. 049, 230 and 343 – respectively on the secularization of cemeteries, on the “governmental sincerity” and on the Decree n. 119A/1890 –; and concludes that the “separation of the two powers” may be a comprehensive formula encompassing not only the laicity of the state but also other socio-political projects.